Are School Reopening Decisions Related to Funding? Evidence from over 12, 000 Districts During the COVID-19 Pandemic. Issue 3 (3rd July 2022) - DeAngelis, Corey A.; Makridis, Christos A.
ABSTRACT: In theory, public school districts with more funding might be more likely to reopen in person if resources are a primary driver of their reopening decisions during the COVID-19 pandemic. However, it is also possible that these decisions are influenced by other factors including political partisanship, incentive structures, and special interests. Using data on over 12, 000 school districts in the United States, we quantify the relationship between public school revenues and expenditures per student and their reopening decisions in Fall 2020. Across a range of statistical specifications, including comparisons of districts within the same county with one another, we find an economically and statistically significant positive association between remote instruction and revenue per student. Our models control for district-level demographic characteristics, together with county COVID-19 risk and partisanship variables. We also find that increases in the share of remote school districts in a state are associated with increases in the growth of counselors and social workers, relative to 2019, even after controlling for the overall employment decline in the state. Our results are consistent with models of rent seeking behavior by teachers unions with unintended consequences on children.